2004
DOI: 10.3758/bf03196888
|View full text |Cite
|
Sign up to set email alerts
|

Memory for thematically arousing events

Abstract: Many studies have indicated that emotional arousal improves memory for the center, or gist, of an event but undermines memory for the event's periphery. However, all of these studies have elicited emotion by showing participants some salient visual stimulus intended to arouse them (e.g., the sight of a wound). This stimulus may have served as an attention magnet, and this, not the arousal, may have been the cause of the observed narrowing of memory. In this article, we examine how participants remember events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
80
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 23 publications
5
80
0
2
Order By: Relevance
“…Indeed, related effects have been reported for spider stimuli (Cole, Balcetis, & Dunning, 2013;Harber, Yeung, & Iacovelli, 2011;Witt & Sugovic, 2013). Third, our displays of rings and dots on otherwise blank backgrounds were schematized, simple, and predictable in their content, and our predisplay descriptions conveyed threat only conceptually Hubbard, 1995Hubbard, , 2005Laney, Campbell, Heuer, & Reisberg, 2004;Laney, Heuer, & Reisberg, 2003;Vinson & Reed, 2002). Thus, our paradigm, which provided for optimal experimental control and comparability between conditions, had rather low ecological validity with respect to threatening situations.…”
Section: Discussionmentioning
confidence: 78%
“…Indeed, related effects have been reported for spider stimuli (Cole, Balcetis, & Dunning, 2013;Harber, Yeung, & Iacovelli, 2011;Witt & Sugovic, 2013). Third, our displays of rings and dots on otherwise blank backgrounds were schematized, simple, and predictable in their content, and our predisplay descriptions conveyed threat only conceptually Hubbard, 1995Hubbard, , 2005Laney, Campbell, Heuer, & Reisberg, 2004;Laney, Heuer, & Reisberg, 2003;Vinson & Reed, 2002). Thus, our paradigm, which provided for optimal experimental control and comparability between conditions, had rather low ecological validity with respect to threatening situations.…”
Section: Discussionmentioning
confidence: 78%
“…Christianson (1992) suggests that the arousal caused by emotive events leads to attentional narrowing whereby eyewitnesses focus on central details at the expense of peripheral details. Laney, Campbell, Heuer, and Reisberg (2004) later demonstrated that this is most likely to occur when emotive events contain salient arousing central details (e.g., a weapon) as they act as "attention magnets".…”
Section: Mood and Eyewitness Memorymentioning
confidence: 99%
“…A third line of research focuses on the relation between affective and nonaffective phenomena. This includes research on the relations between emotions (or their components), moods, and attitudes, on the one hand, and attention, perception, memory, judgments, and decision making, on the other hand (Compton, 2003;Kensinger, 2004;Laney, Campbell, Heuer, & Reisberg, 2004;Levine & Pizarro, 2004;Williams, Mathews, & MacLeod, 1996;Vohs, Baumeister, & Loewenstein, 2007).…”
mentioning
confidence: 99%